Uptake of the proteins HTRA1 and HTRA2 by cells mediated by calcium phosphate nanoparticles - Rotan, Olga (Beilstein J Nanotechnol, 2017)
The efficient intracellular delivery of (bio)molecules into living cells remains a challenge in biomedicine. Many biomolecules and synthetic drugs are not able to cross the cell membrane, which is a problem if an intracellular mode of action is desired, for example, with a nuclear receptor. Calcium phosphate nanoparticles can serve as carriers for small and large biomolecules as well as for synthetic compounds. The nanoparticles were prepared and colloidally stabilized with either polyethyleneimine (PEI; cationic nanoparticles) or carboxymethyl cellulose (CMC; anionic nanoparticles) and loaded with defined amounts of the fluorescently labelled proteins HTRA1, HTRA2, and BSA. The nanoparticles were purified by ultracentrifugation and characterized by dynamic light scattering and scanning electron microscopy. Various cell types (HeLa, MG-63, THP-1, and hMSC) were incubated with fluorescently labelled proteins alone or with protein-loaded cationic and anionic nanoparticles. The cellular uptake was followed by light and fluorescence microscopy, confocal laser scanning microscopy (CLSM), and flow cytometry. All proteins were readily transported into the cells by cationic calcium phosphate nanoparticles. Notably, only HTRA1 was able to penetrate the cell membrane of MG-63 cells in dissolved form. However, the application of endocytosis inhibitors revealed that the uptake pathway was different for dissolved HTRA1 and HTRA1-loaded nanoparticles.